Pointing out persuasion in Philemon - P.B. Decock (Acta Theologica)
This informative and insightful work reveals the vast field of the history and life of the Letter to Philemon after it was written. This approach to biblical texts has received greater attention in recent years when the reader’s contribution to the meaning of texts was first recognised. This attention to the reception of biblical texts is the special subject of the Encyclopedia of the Bible and Its Reception (EBR), which started in 2009 and of which 20 volumes have already been published. This encyclopedia surveys not only sermons and commentaries, but also the various ways in which biblical texts have been received, such as in the creative arts, including paintings, sculptures, novels, films and music. Professor Tolmie’s study, however, focuses on how commentators and preachers have “pointed out persuasion” in this Pauline letter. He has selected, as the subtitle indicates, 50 readings of Philemon from three periods, the early church (starting with Ambrosiaster in chapter 1), the Middle Ages (chapter 2), and the period from the 16th to the 18th century (Chapter 3). For each of these interpreters, Tolmie offers a brief introduction and then focuses on the way they explain the rhetorical situation. He then focuses on the way each author explains the rhetorical strategy by moving through the letter, section by section. Chapter 4, the conclusion, is actually a synthesis, in which Tolmie looks for tendencies in the interpretation of Paul’s letter by focusing first on the way the rhetorical situation is imagined and then on Paul rhetorical strategies in the different literary units of Philemon.